Level of food consumption score and associated factors among households in Konso Zone, Southwestern Ethiopia: a community-based cross-sectional study - Markos, Kasata; Dake, Samson Kastro; Bisetegn, Fithamlak Solomon; Nane, Debritu (Frontiers in Nutrition, 2024)
Background: Despite several attempts made in the developing world to improve overall food consumption patterns, it is still a major problem. However, there is limited literature on evidence of FCS, particularly in the study area.Objective: This study aimed to assess the level of food consumption score and associated factors among households in Konso Zone, southwestern Ethiopia.A community-based cross-sectional study was conducted among 488 households in Konso Zone, southern Ethiopia. Data were collected using an interviewer-administered, pretested, structured questionnaire. We assessed FCS through a seven-day dietary recall of food consumption. The households were labeled as "poor FCS" when they had a food composite score of < 21.5; "borderline FCS" when they had a food composite score of 21.5 -35; and "acceptable FCS" when they had a food composite score of >35 during the reference period. The data were entered into Epi-Data version 3.1 and exported to Statistical Package for Social Science (SPSS) version 25 for analysis. The p-value, adjusted odds ratios (AORs), and 95% confidence intervals (CIs) were used to identify the associated factors.The acceptable FCS among the study participants was 68.3% (95% CI: 63.9, 72.4), whereas 17.4% (95% CI: 14.1, 21.2) were borderline and 14.3% (95% CI: 11.3, 17.8) were poor.There was a higher level of acceptable FCS among households with household heads who were married (AOR = 2.22; 95% CI: 1.08, 4.58), aged 18-24 years (AOR = 0.13, 95% CI: 0.05, 0.30), farmers (AOR = 0.22, 95% CI: 0.13, 0.39), and attended formal education (AOR = 2.68, 95% CI: 1.65, 4.21).The prevalence of acceptable FCS was found to be low. The age of the household head, marital status, occupation, and residence had a significant relationship with the study outcome. Therefore, interventions should target younger-headed and unmarried households.Policies and programs should support the ownership of farmland and promote formal education.